Pengaruh Model Problem Based Learning Berbantuan Media Video Terhadap Hasil Belajar Pendidikan Pancasila Siswa SD - Norita Agustina Subagyo (Journal on Education, 2024)
Pancasila education plays a role in building the spirit of nationalism in the nation's generation. However, learning that is dominated by lecture methods and uses conventional learning media in the form of pictures and writing makes students less interested, resulting in suboptimal learning outcomes. The focus of this trial is to analyze the effect of a learning model centered on problem-solving with video-based media on the learning outcomes of elementary school students. The participants in this trial were 25 fourth-grade students at SD Negeri Ngijo 1 in Semarang City. The approach used was quantitative with an experimental method and a Pre-Experimental research design, specifically the One Group Pretest-Posttest Design type. The findings indicate that the application of the learning model focused on problem-solving with video-based media has been proven to positively influence the improvement of students' learning outcomes.